MANAGEMENT OF PREECLAMPSIA IN PREGNANT WOMEN : LITERATURE REVIEW - Sukmawati Sukmawati; Lilis Mamuroh; Furkon Nurhakim; Yanti Hermayanti (Journal of Maternity Care and Reproductive Health, 2021)
Preeclampsia is a direct cause of maternal death in addition to bleeding and infection. Preeclampsia also causes stunted fetal growth so that it is at risk of threatening the safety of the fetus. Management of preeclampsia is one of the efforts to reduce maternal and infant mortality. This literature review aims to analyze the management of preeclampsia in pregnant women. The database used is Google Scholar,  Science Direct and PubMed with keywords preeclampsia or preeclampsia, pregnant women or pregnant women, management or implementations.The article search results were obtained from Science Direct  124 articles, Google Scholar 1076 and PubMed 252 articles, after screeningobtained from Science Direct 4 articles were, Google Scholar 28 and PubMed 10 articles. The inclusion criteria used werearticles full text, using adesign  randomized controlled trial, experimental and quasi-experimental, using Indonesian and English, published in 2015-2020, a sample of preeclamptic pregnant women and the focus of the nursing intervention literature. There were 9 articles that met the requirements. The results of the analysis showed that the management of preeclampsia includes physical stretching exercises,  stretching exercises versus autogenic training, listening to Ar-Rahman's murottal letter,  Stimulus Cutaneous Slow Stroke Back Massage, psycho-educational counselin, Turkish classical music Turkish classical music, MgSO4 And Slow Stroke Back Massage Therapy, Foot Massage Modification, Foot Massage Modificatio, Warm Footbath With Salt, Slow Sroke Back Massage. The conclusion is that almost all interventions affect blood pressure reduction in pregnant women with preeclampsia.